Out-of-Pocket and Catastrophic Expenditure of Neonatal Health Care in Kaski District, Nepal - Adhikari, Chiranjivi; Sharma, Bishnu Prasad; Subedi, Sudarshan (Economic Journal of Development Issues, 2018)
Neonatal mortality is the prime indicator that contributes to child mortality. The out-of-pocket (OOP) expenditure for treatment remains a major barrier in treatment. The study aimed to calculate OOP of neonatal health care in Kaski district of Nepal. A total of 450 mothers (226 from rural and 224 from urban), having infants aged six months or less or the infants died within last six months, were interviewed face-to-face retrospectively for neonate period. Firstly, six out of 33 urban and ten out of 43 rural clusters were randomly selected from Kaski district and secondly, within each cluster, HHs were selected using EPI method as described by WHO. The mean out-of-pocket expenditure (OOP) of neonatal health care was NRs. 4,322 which was 2.7 percent of total non-food expenditure. Three percent HHs suffered catastrophic health expenditure due to neonatal OOP. It reached five percent when housing/rental cost was excluded from non-food expenditures. HHs with cases of ARI, diarrhea, and others such as Neonatal Tetanus (NT), constipation, eye infection, preterm, meconium engulf and allergy differed significantly from the HHs with cases of jaundice and fever at all three thresholds of catastrophic health expenditure. OOP also differed significantly according to the levels of health facilities. Economic Journal of Development Issues Vol. 21 & 22 No. 1-2 (2016) Combined Issue, Page: 1-21